2017
DOI: 10.1108/ijdrbe-10-2015-0046
|View full text |Cite
|
Sign up to set email alerts
|

Analysing community needs and skills for enhancing disaster resilience in the built environment

Abstract: Purpose -A better cooperation among all the stakeholders working towards enhancing the disaster resilience of societies can only be achieved if the expectations or the needs of each stakeholder are understood. This study attempts to outline the needs of communities affected by disasters for the purpose of aligning the needs and skill requirements with the abilities of built environment professionals serving these communities. Therefore, the study aims to identify and describe community needs and skill requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This type of approach was in line with case studies and field studies such as observation, documentation and categorization of the phenomena. These data was elicited from interview (Perera et al, 2017;Pollock et al, 2019;Rahman and Kausel, 2012;Drolet et al, 2015;O'Neill et al, 2016), semi-structured interviews (Houston et al, 2019), group interview (Alaedini et al, 2011;Arneson et al, 2017;Comes et al, 2019), in-depth interviews (Gultom and Joyce, 2014;Cretney, 2016), focus group (Golding et al, 2020;Mosley et al, 2012), field work (Murphy et al, 2014), forum design (Wells et al, 2013;Berke et al, 2011;Dufty, 2017), content analysis (Firdhous and Karuratane, 2018;Herath et al, 2020;Hong et al, 2018), participatory action research (Miles, 2018), document analysis (Sulaiman and Fernando, 2019), ethnographic research (McIlvaine-Newsad et al, 2020), constructivist research (Bacud, 2018), meeting through ergonomics framework (da Silva et al, 2015) and critical review of the literature (Satria et al, 2012). A SLR of community disaster resilience One-third of the studies were quantitative.…”
Section: Results Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This type of approach was in line with case studies and field studies such as observation, documentation and categorization of the phenomena. These data was elicited from interview (Perera et al, 2017;Pollock et al, 2019;Rahman and Kausel, 2012;Drolet et al, 2015;O'Neill et al, 2016), semi-structured interviews (Houston et al, 2019), group interview (Alaedini et al, 2011;Arneson et al, 2017;Comes et al, 2019), in-depth interviews (Gultom and Joyce, 2014;Cretney, 2016), focus group (Golding et al, 2020;Mosley et al, 2012), field work (Murphy et al, 2014), forum design (Wells et al, 2013;Berke et al, 2011;Dufty, 2017), content analysis (Firdhous and Karuratane, 2018;Herath et al, 2020;Hong et al, 2018), participatory action research (Miles, 2018), document analysis (Sulaiman and Fernando, 2019), ethnographic research (McIlvaine-Newsad et al, 2020), constructivist research (Bacud, 2018), meeting through ergonomics framework (da Silva et al, 2015) and critical review of the literature (Satria et al, 2012). A SLR of community disaster resilience One-third of the studies were quantitative.…”
Section: Results Of the Studymentioning
confidence: 99%
“…This also includes risk management (Firdhous and Karuratane, 2018), communication (Liu, 2020; Spialek and Houston, 2019), crisis communication (Gultom and Joyce, 2014), information deficits (Arneson et al , 2017), information system (Muto and Kohtake, 2017) and information asymmetries (Comes et al , 2019). Novel approaches were designed for fostering citizen and disaster mitigation; preparedness, response, recovery and resilience such as environmental disasters (Rifat and Liu, 2020); industry-related needs and skills for enhancing disaster resilience in stakeholder perspectives (Perera et al , 2017); disaster journalism (Houston et al , 2019); postdisaster projects (Tōhoku Dionisio and Pawson, 2016); barriers to disaster risk reduction and resilience (Imperiale and Vanclay, 2020) and protect, accommodate, retreat or avoid (PARA) for flood disaster risk reduction and resilience (Doberstein et al , 2019).…”
Section: Results Of the Studymentioning
confidence: 99%
“…Eventually, 29 educational needs (i.e. knowledge gaps) were identified (listed earlier); this aspect of the study is reported in more details in Perera et al (2017) (part of Collaborative Action towards Disaster Resilience Education [CADRE] research outputs). This research progressed with a comprehensive desk review involving four researchers and academics in the built environment.…”
Section: Methodsmentioning
confidence: 99%
“…Both researchers and practitioner groups agree that it is necessary to maximize community resilience benefits. The community skill requirements for enhancing disaster resilience were considered to relate to building environment professionals and five disaster resilience dimensions, which include society, economy, technology, environment, and institutions [ 107 ]. Several resilience enhancement strategies, including innovative models and methods, have been proposed.…”
Section: The Three Phases Of Urban Disaster Resilience Researchmentioning
confidence: 99%